Չարխափան Ս. Աստուածածնի սրբապատկերը - Տամատեան, Յարութիւն Աբղյ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Со знаменитыми монастырями Константинопольской патриархии тесно связан образ Отгоняющей зло Пресвятой Богородицы (Чархапан Сурб Аствацацин), благодаря которому монастырь назван Чархапан Сурб Аствацацин. В истории монастыря образ упоминается также своими чудесами. Кроме того, некогда действующая в квартале Каракёй Константинополя церковь Св. Иоанна Златоуста (Сурб Ован Воскеберан), где также был образ «Чархапан Сурб Аствацацин» (Отгоняющей зло Пресвятой Богородицы) называли «Покр Армаш» (Маленький Армаш) и была тесно связана с упоминанием монастыря Армаша. Чудотворный образ Армаша в 1920-ые был утерян. А чудотворный образ в квартале Каракёй в 1900 г. был перенесен в Палат. Ныне память об Отгоняющей зло Пресвятой Богородицы остается живой благодаря одноименным образам, сохранившимся в церквях Свв. Архангелов (Сурб Рештакапетац) в Палате, Св. Креста (Сурб Хач) в Нью-Йорке и Св. Царя в Гатегюхе. One of the most famous monasteries of the Armenian Patriarchate of Constantinople, Armash Monastery, is closely related with Charkhapan Soorp Asdvadzadzin’s (Evil Expeller Holy Mother of God) icon. That’s why the monastery was called as “Charkhapan Soorp Asdvadzadzin” Monastery. In the historical path of the monastery, the icon was remembered with miracles. In addition, by a similar Charkhapan icon, the former St. Hovhan Vosgeperan (John Chrysostom) Armenian Apostolic Church of Karagumruk was called “Small Armash” and was closely related to the memory of Armash Monastery. The miraculous icon of Armash was lost in the 1920s, and the miraculous icon of Karagumruk was moved to Balat in 1900. Today, the memory of Charkhapan continues on display in the Balat Soorp Hreshdagabed (Holy Archangel), New York, Uptown Soorp Khach (Holy Cross) and Kadikoy (Chalcedon) Soorp Takavor (Holy King) Armenian churches with their Charkhapan icons.
Keywords: Կրօնագիտութիւն